2015
DOI: 10.7556/jaoa.2015.061
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Pump Treatment as an Adjunct to Antibiotics for Pneumonia in a Rat Model

Abstract: The results suggest that 3 applications of LPT induces an additional protective mechanism when combined with levofoxacin and support its use as an adjunctive therapy for the management of pneumonia; however, the mechanism responsible for this protection is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…It is important to realise that, while basic or primary experimental research may support the plausibility of a variety of mechanisms that produce changes to the tissues or nervous system, there remains a lack of clinical evidence that establishes these changes as relevant and meaningful to clinical outcomes in patients. Some of these plausible, but speculative, therapeutic mechanisms affecting the tissues include drainage of tissue fluids and pro-inflammatory metabolites from injured joints and tissues [21][22][23], short-term changes in joint pressure and motion due to joint tribonucleation and cavitation [24,25], manipulation of extrapped zygapophyseal meniscoid folds [24,26], promotion of tissue healing and collagen remodelling following injury [27][28][29], reduced thickness (densification) and improved viscosity of the loose connective tissue layer in deep fascia [30,31], mechanotransduction 5 and anti-inflammatory cellular responses of fibroblasts [32][33][34][35][36], improvement in sensory motor integration [37][38][39] and proprioception [40][41][42][43], parasympathetic responses following gentle techniques to the neck and head [44][45][46], and increased lymph flux, circulating lymphocytes, and immunity from abdominal lymphatic pump techniques [47][48][49][50].…”
Section: Therapeutic Mechanisms Of Manual Therapymentioning
confidence: 99%
“…It is important to realise that, while basic or primary experimental research may support the plausibility of a variety of mechanisms that produce changes to the tissues or nervous system, there remains a lack of clinical evidence that establishes these changes as relevant and meaningful to clinical outcomes in patients. Some of these plausible, but speculative, therapeutic mechanisms affecting the tissues include drainage of tissue fluids and pro-inflammatory metabolites from injured joints and tissues [21][22][23], short-term changes in joint pressure and motion due to joint tribonucleation and cavitation [24,25], manipulation of extrapped zygapophyseal meniscoid folds [24,26], promotion of tissue healing and collagen remodelling following injury [27][28][29], reduced thickness (densification) and improved viscosity of the loose connective tissue layer in deep fascia [30,31], mechanotransduction 5 and anti-inflammatory cellular responses of fibroblasts [32][33][34][35][36], improvement in sensory motor integration [37][38][39] and proprioception [40][41][42][43], parasympathetic responses following gentle techniques to the neck and head [44][45][46], and increased lymph flux, circulating lymphocytes, and immunity from abdominal lymphatic pump techniques [47][48][49][50].…”
Section: Therapeutic Mechanisms Of Manual Therapymentioning
confidence: 99%
“…Recent evidence from animal models suggests these techniques may not only increase lymphatic flow [92] and lymphocytes in circulation [93], but also augment the immune response [94]. Lymphatic pump techniques in animal models have also been reported to inhibit the growth of Streptococcus pneumoniae bacteria in the lungs [95,96]. These animal studies suggest potentially important health outcomes from lymphatic pump techniques, but their generalisability to humans is yet to be explored and should still be regarded as speculative.…”
Section: Movement Of Fluidsmentioning
confidence: 99%
“…However, there may be additional mechanisms-still largely speculative-that potentially enhance general health. Based on animals models, lymphatic pump techniques increased lymphatic flow [92] and augmented the immune response [93][94][95][96], and this approach potentially could have clinical relevance. Some manual approaches produce a strong parasympathetic effect [159][160][161], which may be clinically relevant for people who are chronically stressed and anxious.…”
Section: Functionmentioning
confidence: 99%
“…37 Animal studies also show that the efficiency of antibiotics to diminish the bacterial load in acute pneumonia is significantly improved when associated with pump techniques. 38 Lastly, Walkowski et al have shown that OMT induces an increase of specific immune cells not only in the lymphatic circulation but in the peripheral blood circulation as well, supporting the idea of a direct influence of OMT on immunity. 33 …”
Section: Inflammatory Biochemical Pathwaysmentioning
confidence: 90%